Morphological characteristics of preliminary breakdown pulses of hybrid intra cloud–negative cloud-to-ground lightning at low lattitude. (August 2019) - Emeraldi, P; Hamid, M I; Hazmi, A
Abstract: Preliminary breakdown (PB) pulses can represent the propagation path of lightning initiation and can be used to model the charge structure of a thundercloud. The characteristics of PB pulses from the lightning initiation process depend on the charge structure of the lightning cloud. This study presents the PB pulse morphology and charge structure of thunderclouds from hybrid intracloud–negative cloud-to-ground (hybrid IC-NCG) lightning in Padang, Indonesia. PB pulses were obtained from lightning radiation electric field observation. A total of 41 PB pulse waveforms of hybrid IC-NGC flashes were analyzed. Three types of PB pulse characteristics occurred in association with three different types of hybrid IC-NCG lightning morphologies. Hybrid IC-NCG lightning can be initiated from the main negative cloud charge to the upper positive cloud charge or vice-versa. The propagation direction of the initial PB pulse train of hybrid IC-NCG flashes is either upward or downward.